Ciprofol Versus Propofol for Sedation in Gastrointestinal Endoscopy: A Systematic Review and Meta-Analysis in a Chinese Population - Yang H; Lai P; Qin X; Cui Y; Zhang X; Zhang H; Ding Y; Ye E; Wu Y; Ren B (Drug Design, Development and Therapy, 2025)
Hongyu Yang,1,* Ping Lai,1,* Xiaoyu Qin,2,* Yiyang Cui,3 Xiaojia Zhang,4 Haiqing Zhang,2 Yichen Ding,2 Ersheng Ye,2 Yaping Wu,5 Bingxu Ren2 1Department of Anesthesiology, Nanchang People’s Hospital, Nanchang, Jiangxi, People’s Republic of China; 2Department of Anesthesiology, Shanghai East Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 3Department of Anesthesiology, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of China; 4Department of Anesthesiology, Hebei General Hospital, Shijiazhuang, Hebei, People’s Republic of China; 5Cadre Ward (Geriatrics Department), The 81st Group Military Hospital of the Chinese People’s Liberation Army, Zhangjiakou, Hebei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoyu Qin, Department of Anesthesiology, Shanghai East Hospital, School of Medicine, Tongji University, No. 551, Pudong South Road, Pudong New Area, Shanghai, 200120, People’s Republic of China, Email qxyznl@163.comPurpose: Ciprofol (HSK3486) is a novel intravenous anesthetic structurally similar to propofol; however, its advantages over propofol remain unclear. This study aimed to compare the safety, efficacy, and satisfaction outcomes of ciprofol and propofol during gastrointestinal endoscopy.Patients and Methods: This systematic review incorporated all available comparative trials assessing ciprofol versus propofol for endoscopic sedation following a comprehensive search strategy across eight biomedical databases—Web of Science, Embase, PubMed, and Cochrane Library, along with major Chinese repositories (CNKI, Wanfang, CBM, and VIP)—through September 2023. Evidence synthesis was conducted per PRISMA guidelines, with methodological rigor enhanced through prospective trial registry screening and implementation of GRADE framework for evidence grading.Results: This systematic review included 45 randomized controlled trials involving 6884 patients who met predefined methodological and clinical eligibility thresholds. Very low to moderate certainty evidence showed that ciprofol induced sedation or anesthesia comparable to that of propofol (relative risk [RR]: 1.00, 95% confidence interval [CI]: 1.00 to 1.01), with both agents demonstrating similar procedural efficiency. Furthermore, ciprofol was associated with a reduced incidence of complications, including hypotension (RR: 0.60, 95% CI: 0.51 to 0.70), bradycardia (RR: 0.69, 95% CI: 0.56 to 0.85), nausea and vomiting (RR: 0.67, 95% CI: 0.54 to 0.84), hypoxia (RR: 0.38, 95% CI: 0.31 to 0.48), respiratory depression (RR: 0.39, 95% CI: 0.28 to 0.56), apnea (RR: 0.35, 95% CI: 0.23 to 0.53), and injection pain (RR: 0.13, 95% CI: 0.09 to 0.17), while also enhancing patient and anesthesiologist satisfaction.Conclusion: Ciprofol-induced sedation or anesthesia was comparable to propofol, with both drugs demonstrating similar procedural efficiency. However, ciprofol was associated with lower risk of adverse reactions and higher satisfaction among patients and anesthesiologists. Ciprofol may represent a superior sedative option for gastrointestinal endoscopy.Keywords: sedation, systematic review, gastrointestinal endoscopy